The concept of world hegemony and the understanding of international cooperation and regulation: A critical reading of the current conceptualizations of world hegemony. - Choukri, Ezz-Edine. (University of Ottawa (Canada), 1995)
This thesis questions the utility of the concept of "world hegemony" in understanding world politics. In doing so, it reviews the ways in which both Realist and Marxist traditions used that concept to study three examples of international regulation: the GATT, the global environmental negotiations, and the Coordinated Aid to Russia. This review shows the limited explanatory power of both Realist and Marxist conceptions of hegemony. Based on the analysis of modernity presented by Karl Polanyi and Anthony Giddens, the thesis presents a new conception of world hegemony that refers to the centuries-long build-up of consensus and consent around a modern and global historic bloc. The latter includes market-economy, interstate system, individualism and human emancipation. The analysis of the interactions between actors and this multidimensional global historic bloc provides better understanding of the three examples of international regulation used in the thesis.
Keywords: Political Science, International Law and Relations.